Ultrasound-guided thrombin injection versus ultrasound-guided compression therapy of iatrogenic femoral false aneurysms: Single center experience - Rashaideh, Mohammed A. (Med J Armed Forces India, 2020)
BACKGROUND: Iatrogenic femoral pseudoaneurysm (false aneurysm) due to arterial access following cardiovascular procedures is becoming common because of the increase in number and complexity of the procedures. Recently, percutaneous thrombin injection is becoming a popular treatment of these false aneurysms. The aim of this study was to assess the efficacy and safety of femoral pseudoaneurysm closure using ultrasound-guided thrombin injection in comparison to ultrasound-guided compression. METHODS: A retrospective analysis was undertaken of 65 patients who presented to our vascular department with iatrogenic femoral pseudoaneurysm between January 2015 and March 2019. Twenty-five patients underwent ultrasound-guided thrombin injection, and 40 were treated using ultrasound-guided compression therapy. The primary outcome measured was efficacy, while other outcomes examined were safety, procedure duration, and cost. RESULTS: A total of 65 patients (45 males, 20 female) were identified with a mean age of 62 years. Out of the 65, 40 patients (28 males, 12 female) underwent ultrasound-guided compression therapy (group A) with a mean aneurysm size of 2.9 cm, and 25 (17 male, 8 female) underwent ultrasound-guided thrombin injection (group B) with a mean pseudoaneurysm sac size of 3.7 cm. The success rate of thrombosis in group A was 70% and in group B was 92%. No significant complications were reported in both groups. CONCLUSIONS: Ultrasound-guided thrombin injection should be considered as the first line of treatment for uncomplicated femoral pseudoaneurysms because it has a higher thrombosis and lower recurrence rates, when compared with ultrasound-guided compression treatment.